Use of magnetic particles in the purification of igm antibodies against taenia solium - Perez L.A. (2020)
The use of L protein coupled magnetic particles for the concentration and purification of immunoglobulin M (mIgM) monoclonal antibodies against Taenia solium was evaluated. Three concentration methods and different elution times were evaluated and the ratio of particles to the ratio of mIgM was optimized. It is demonstrated that: 1) with the use of magnetic particles, a previous concentration of mIgM is not required, which reduces the manipulation of the antibodies and improves the recovery, 2) the use of a binding buffer can be omitted, since the pH of most cell culture supernatants are neutral, and 3) longer elution times (~ 45 minutes) are needed to increase recovery to a level greater than 80%. The study demonstrates that the use of L protein-coupled magnetic particles is a simple and efficient tool for mIgM concentration and purification. © 2020, Instituto Nacional de Salud. All rights reserved.